FATTY ACID PROFILE OF FROZEN FILLETS OF COBIA (Rachycentron canadum) STUNNED BY ELECTRONARCOSIS - Fúlvio Viegas Santos Teixeira MELO (Boletim do Instituto de Pesca, 2020)
The objective of this research was to evaluate the effect of desensitisation by electronarcosis on the changes to the fatty acid profile of cobia (Rachycentron canadum) fillets stored at low sub-zero temperature. For stunning, 50, 100 and 150 V were used for 120 s and then exsanguination was performed, followed by storage at –18 °C for 180 days. A total of 47 fatty acids were detected in cobia fillet samples, and most of the quantified fatty acids differed (p < 0.05) between treatments and storage times. The n6/n3 ratio did not differ (p > 0.05) among treatments; however, the n6/n3 ratio and Σhypocholesterolaemic fatty acids Ʃhypercholesterolaemic fatty acids ratio were significantly affected by the storage times and their outcomes. In general, the electronarcosis intensities used to numb cobia did not promote differences during the frozen storage of the fillets for most of the analysed variables but a significant effect of the storage time was noted within the treatments, with meat quality loss observed over time.